Factors limiting productivity of the Central Arctic Caribou Herd of Alaska - Haskell, Shawn P.; Ballard, Warren B. (Rangifer, 2004)
Many biotic and abiotic factors can limit productivity and growth of caribou (Rangifer tarandus) herds, but limiting factors typically vary by region. Identifying limiting factors may help to indicate which seasons are of relative importance to a caribou herd and possibly to suggest general life history strategies. Using regression techniques, we found that despite previous suggestions, net productivity of Alaska’s Central Arctic Caribou Herd (CAH) did not respond to early summer forage biomass or summer insect severity from the previous year. Abiotic factors that did have apparent effects on CAH productivity included early fall snow deposition, winter snow condition, and spring snow ablation. To achieve a suitable weight for conception, caribou of the CAH may exhibit a seasonal time-minimizing foraging strategy by moderating weight gain during the warm summer insect season and feeding more intensively during the insect-free weeks before the autumn rut. A long-term trend of the Northern Hemisphere annular mode (NAM) may be linked to anthropogenic climate change and may have negative implications for the future success of the CAH.